2016
DOI: 10.19106/jmedsciesup0048042016019
|View full text |Cite
|
Sign up to set email alerts
|

miR-21, miR-29c, and miR-155 as biomarker to develop minimally-invasive diagnostic in hepatocellular carcinoma patient

Abstract: Hepatocellular carcinoma (HCC) is one of the most prevalent malignancies and the third leading cause of cancer-related deaths worldwide. HCC carries poor prognosis, its incidence and mortality increase annually. The most common hypothesis explaining the problem is the cell's high tendency to metastasize and recur, even after surgical treatment. Therefore, it is important to find new serological biomarkers to detect HCC in early stages. Plasma microRNAs are being actively investigated as minimallyinvasive bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It showed that increasing regulations in miRNA 21-5p and miRNA 155-5p (1.74 and 1.55 folds); while in miRNA 29c-3p, there was decreasing regulation of 1.83-fold ( Table 1 ). Based on the fold change analysis, miRNA 29c-3p may be acting as a tumor suppressor, and oppositely, miRNA 21-5p and miRNA 155-5p may act as onco-miR [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It showed that increasing regulations in miRNA 21-5p and miRNA 155-5p (1.74 and 1.55 folds); while in miRNA 29c-3p, there was decreasing regulation of 1.83-fold ( Table 1 ). Based on the fold change analysis, miRNA 29c-3p may be acting as a tumor suppressor, and oppositely, miRNA 21-5p and miRNA 155-5p may act as onco-miR [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The three miRNAs might be detected in HCC and could be used as minimally invasive biomarkers in HCC detection. The miRNA-155 expression levels showed significant elevation in HCC tissue with an increase of 1.5–6 times compared to normal liver tissue [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%